Local identity as an amplifier: procedural justice, local identity and attitudes towards new dam projects - Marques, S. (2015)
Local environmental changes are complex processes that are not always easily accepted by the communities. Research has shown that perceived procedural justice is a key variable in understanding these debates. From a perspective based on Social Identity Theory, we hypothesize in this paper that this effect will be particularly stronger for those that have a high degree of place identity, at least in the early stages of such projects. Results based on two large-scale studies conducted on sites where two dams were projected to be built support our hypotheses (Studies 1, N = 248 and Study 2, N = 385), and show that these results stand, even after controlling for demographic factors, perceived trust and expected outcomes of the project for the region. These results are discussed based on the implications they have for project communication and management in early stages of project implementation. (C) 2015 Elsevier Ltd. All rights reserved.